عوامل الاستقرار الأسري دراسة فقهية مقاصدية - • عوينة قمير; • بشير نعمة الله (جامعة محمد بوضياف, 2025)
تتناول هذه الدراسة موضوع الاستقرار الأسري من منظور فقهي مقاصدي، حول بيان طبيعة العلاقة الشرعية التي تربط بين الزوجين، بوصفها ميثاقًا غليظًا يقوم على أسس مشروعة، وتهدف إلى الكشف عن العوامل المؤثرة في هذا الرباط، سواء قبل الزواج أو بعده، والتي يُمكن، إذا تمسّك بها الشاب المقبل على الزواج، أن تُسهم في بناء أسرة مستقرة وآمنة. ورغم توفر هذه العوامل، فإن التغيرات الاجتماعية والمعيشية في الواقع الحضري المعاصر كان لها أثر واضح على استقرار الحياة الزوجية، مما أفضى إلى عدد من النتائج، من أبرزها: ضرورة حسن الاختيار، وتحقق الكفاءة بين الزوجين، ورفع مستوى الوعي، فضلًا عن أهمية تأهيل المقبلين على الزواج اعدادا لهم وتمكينا من تجاوز التحديات المحتملة، والحفاظ على استقرار العلاقة الزوجية. this study addresses the topic of family stability from a juristic and Maqasid-based perspective (higher objectives of Islamic law). It explores the nature of the legal relationship that binds the spouses, describing it as a solemn covenant based on legitimate foundations. The study aims to uncover the factors that influence this bond, both before and after marriage, which-if upheld by a young person intending to marry-can contribute to building a stable and secure family. Despite the availability of such factors, social and living changes in modern urban life have had a noticeable impact on the stability of marital life. This has led to several key conclusions, most notably: the necessity of proper spouse selection, compatibility between partners, raising awareness, and the importance of preparing those intending to marry. Such preparation aims to equip them to face potential challenges and maintain a stable marital relationship.